A new species of Cyperus L. (Cyperaceae) from northeastern Brazil - Ribeiro, André Rodolfo De Oliveira; Alves, Marccus; de Oliveira, Regina Célia (Phytotaxa, 2015)
A new species, Cyperus potiguar, is here described and illustrated. It is a perennial species morphologically related to C. alvesii and C. ligularis, but can be recognized by spikelet size, number and size of glumes, and length of rachilla internodes. It is found in the semi-arid vegetation of northeastern Brazil, locally called Caatinga.